2015
DOI: 10.1097/mph.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Anti-M Antibody Induced Prolonged Anemia Following Hemolytic Disease of the Newborn Due to Erythropoietic Suppression in 2 Siblings

Abstract: Hemolytic disease of the newborn (HDN) arising from MNSs incompatibility is rare, with few reports of prolonged anemia and reticulocytopenia following HDN. We report the younger of 2 male siblings, both of whom had anti-M-induced HDN and anemia persisting for over a month. Peripheral reticulocytes remained inappropriately low for the degree of anemia, and they needed multiple red cell transfusions. Viral infections were ruled out. Corticosteroids were given for suspected pure red cell aplasia. Anemia and retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 13 publications
1
23
0
5
Order By: Relevance
“…In addition, a characteristic of low‐temperature reactivity was also shown for the IgG component of alloanti‐M. For instance, when the alloanti‐M and the titer were tested in one Japanese newborn's serum, the levels were undetectable by saline‐IAT at 37 °C, 1:16 in saline at room temperature and 1:64 in saline at 4 °C, while the DAT of RBCs was negative . A similar reaction pattern of IgG alloanti‐M was found in our study and reported by another Chinese reference lab .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, a characteristic of low‐temperature reactivity was also shown for the IgG component of alloanti‐M. For instance, when the alloanti‐M and the titer were tested in one Japanese newborn's serum, the levels were undetectable by saline‐IAT at 37 °C, 1:16 in saline at room temperature and 1:64 in saline at 4 °C, while the DAT of RBCs was negative . A similar reaction pattern of IgG alloanti‐M was found in our study and reported by another Chinese reference lab .…”
Section: Discussionsupporting
confidence: 89%
“…A series of data showed that abortion occurred more often in the first trimester, anemia occurred much earlier, and hydrops fetalis or stillbirth occurred in MN alloimmunization more than Rh alloimmunization, indicating that anemia caused by alloanti‐M could happen at a very early stage of pregnancy and that hyporegeneration of erythroblast rather than hemolysis should play a critical role for anemia in this stage . Similar to anti‐K being able to suppress erythropoiesis through inhibiting the growth of Kell‐positive erythroid precusor cells, there are also some primary studies to show that alloanti‐M could inhibit the growth of M‐positive colony‐forming units in vitro, as M antigen is expressed on immature erythroid precursors as early as 9 weeks of gestation and fully developed on mature RBCs at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Yasuda et al collated all 33 reported Japanese cases, finding an association with reticulocytopenia and the severity of anemia. This likely represents antibody binding to M+ erythroblasts reducing erythropoiesis and has been described by others . Yasuda et al also found that one‐third of cases occurred with low titer anti‐M.…”
Section: Discussionmentioning
confidence: 53%
“…Antibodies to this antigen are common but are nonpathogenic because they typically react below body temperature at 4°C . However, due its ability to bind to these select progenitor cells, the anti‐M antibody has been implicated in development of delayed transfusion reactions, hemolytic disease of the newborn, and red cell aplasia through inhibition of red cell precursor growth . Blood transfusions are a known risk factor for blood‐group antibody development .…”
Section: Discussionmentioning
confidence: 99%